Stabilization flyuorytopodibnoyi structure in oxide vacuum condensate - Заславський, О.М. (Proceedings of National Aviation University (archive), 2006)
The influence of the oxide-stabilizer content, M’-cation radius and film deposition temperature on the stabilization of the fluorite-like solid solutions in the zirconium and hafnium oxides-based vacuum condensates, obtained by Laser-evaporating method, was investigated. The optimum parameters of the coatication of the isotropic thermostable coverings was determined. This results were explained by using of the high-speed condensation in vacuum theory.